2023
DOI: 10.2147/jaa.s420328
|View full text |Cite
|
Sign up to set email alerts
|

Common Allergens and Immune Responses Associated with Allergic Rhinitis in China

Qirong Li,
Xinyi Zhang,
Qiang Feng
et al.

Abstract: Allergic rhinitis (AR) is a chronic allergic disease of the upper respiratory system that affects approximately 10-40% of the global population. Due to the large number of plant pollen allergens with obvious seasonal variations, AR is common in China. AR is primarily caused by the abnormal regulation of the immune system. Its pathophysiological mechanism involves a series of immune cells and immune mediators, including cytokines. The present review summarizes the common allergens in China and the complex patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 118 publications
0
4
0
2
Order By: Relevance
“…China has a vast territory, with geographical and climatic environments characterized by North, South, East, and West, and a wide variety of plant species 38 . This is the main reason for the significant geographical differences in pollen allergens in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China has a vast territory, with geographical and climatic environments characterized by North, South, East, and West, and a wide variety of plant species 38 . This is the main reason for the significant geographical differences in pollen allergens in China.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyzing the pollen prevalence in the seven regions, it was found that the sensitization of tree and grass pollen was mainly distributed in North China and Northeast China. By comparing the allergenic pollen species and dispersal patterns in each geographical region of China, it was found that the main allergenic pollens in Northeast China were summer and autumn pollen and Artemisia, with Artemisia pollen occupying the first place in terms of quantity and allergenicity 38 , 40 . In North China, spring allergenic pollens were dominated by Elm, Pinus, Populus, and Pinus, while autumn pollens were common in Artemisia, Quinoa, and Humulus 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Собственный аллергоанамнез: у ребенка АР, персистирующий, легкой степени тяжести. Детский сад посещает 6 GINA Difficult-to-treat & Severe Ashtma in adolescent and adult patients. с 2,5 года.…”
Section: клинический примерunclassified
“…Воспаление слизистой оболочки носа, опосредованное иммуноглобулином Е (IgE), вызванное аллергенами, является основополагаю щим патофизиологическим механизмом АР [5]. Общие клинические проявления АР включают чихание, зуд, ринорею или заложенность носа [6]. Нередко сопутствуют покраснение глаз и слезоточивость.…”
Section: Introductionunclassified
“…Eosinophils in the nasal mucosa are also activated during this process. Nasal epithelial injury exposes nerve fibers and promotes the release of granule contents, which elicit T helper 2 cell (Th2) response, resulting in the recruitment of eosinophils, basophils, and T cells to sustain the inflammatory response ( 8 ). Th17 and regulatory T (Treg) cells, rather than the traditional Th1/Th2 balance paradigm, were recently reported to mediate AR pathogenesis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%